PENGEMBANGAN MEDIA VIDEO PEMBELAJARAN DENGAN MENGGUNAKAN APLIKASI CAMTASIA PADA MATERI JENIS-JENIS PEKERJAAN PEMBELAJARAN TEMATIK KELAS IV SEKOLAH DASAR - Awaliyah, Siti Echa Robiatul; Nurhasanah, Ana; Hakim, Zerri Rahman (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2024)
The quality of learning can be seen from a teacher being able to understand and apply the competencies that should be mastered by teaching staff. As science and technology develop, teachers are required to be able to develop computer competencies and skills, the use of information and communication technology, one of which is skills in creating learning media. Using media can also help students not get bored in learning and can involve students in learning activities in class. During the learning process teachers only use conventional media such as theme books and media in the form of images, therefore a variety of learning media is needed. This research aims to determine the development and feasibility of video media using the Camtasia application for material on types of thematic learning work for class IV elementary schools. Researchers used the Research and Development (R&D) method using the 4D (Four-D) model define, design, develop, and disseminate. The research results that show the feasibility of developing video media are based on the assessment of media experts and material experts. The assessment results from the two media expert validators received a score of 89%, including the